2007
DOI: 10.1021/jp066972w
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Cleavage Mechanism of Methylcobalamin:  Elementary Steps of Co−C Bond Breaking

Abstract: Density functional theory has been applied to the investigation of the reductive cleavage mechanism of methylcobalamin (MeCbl). In the reductive cleavage of MeCbl, the Co-C bond is cleaved homolytically, and formation of the anion radical ([MeCbl]*-) reduces the dissociation energy by approximately 50%. Such dissociation energy lowering in [MeCbl]*- arises from the involvement of two electronic states: the initial state, which is formed upon electron addition, has dominant pi*corrin character, but when the Co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
96
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(116 citation statements)
references
References 49 publications
19
96
1
Order By: Relevance
“…The Becke and Perdew functional forms (BP86) were used for exchange and correlation interactions, respectively [28,29]. This functional form has been previously used in DFT studies on metal-based bioinorganic systems and showed to provide accurate geometries [16,[30][31][32][33][34][35][36]. Since the BP86 is known to underestimate the energy barrier for hydrogen atom transfers [37], the energy values were further refined using the hybrid B3LYP functional [38][39][40].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The Becke and Perdew functional forms (BP86) were used for exchange and correlation interactions, respectively [28,29]. This functional form has been previously used in DFT studies on metal-based bioinorganic systems and showed to provide accurate geometries [16,[30][31][32][33][34][35][36]. Since the BP86 is known to underestimate the energy barrier for hydrogen atom transfers [37], the energy values were further refined using the hybrid B3LYP functional [38][39][40].…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, even with this barrier, a kinetic calculation shows that fast bond cleavage is improbable. Furthermore, the energy barrier of the Co-C bond breaking is much higher for base-on compared to the base-off species [39,68,106]. Our estimations show that the energy barrier of the geometry optimized 1e-reduced base-on specie is higher by about 0.5 eV compared to the energy barrier of the geometry optimized 1e-reduced base-off specie (see Figure 7 for single points calculations).…”
Section: Density Functional Theory (Dft) and Quantum Mechanics/ Molecmentioning
confidence: 69%
“…This enters a fl agrant contradiction with the experimental data, which demonstrates that the reaction rate constant of Co-C bond breaking is much higher in base-on species compared with the same reaction rate constant for base-off species [38]. Moreover, base-off methylcob(II)alamin compound cannot be considered in Co-C bond cleavage reaction of bio-reactions since is predicting a four coordinate vitamin B 12 specie immediately after a Co-C bond cleavage of methylcobalamin compound [39,68,106]. Instead, several experimental results show that methylco(II)calamine cofactor is fi ve coordinate [23][24][25][26][27][28]101,102] immediately after Co-C bond cleavage.…”
Section: Density Functional Theory (Dft) and Quantum Mechanics/ Molecmentioning
confidence: 72%
See 1 more Smart Citation
“…The BP86 functional has been previously selected as the most appropriate for predicting both the structural and electronic properties of B 12 cofactors, including Co-C bond dissociation energy (BDE) (Jensen and Ryde, 2003; Rovira et al, 2004; Kuta et al, 2006; Kozlowski et al, 2007; Rovira and Kozlowski, 2007; Galezowski et al, 2008; Lodowski et al, 2009, 2011; Kornobis et al, 2011, 2013). To account for environmental effects on geometries and electronic properties, ground states of RibCbl model (Im-[Co III (corrin)]-Rib + , see Figure S1) were computed in the gas phase as well as in water via the Polarizable Continuum Model (PCM) (Miertuš et al, 1981; Cammi and Tomasi, 1995) as implemented in Gaussian 09.…”
Section: Computational Detailsmentioning
confidence: 99%